Microin the Aquatic Environment: A Hidden Threat that Pollutes the Future - Albakaa, Zahirah Abbas Ali; Alzurfi, Sadiq Kadhum Lafta (Journal of Science in Medicine and Life, 2025)
Recent decades have witnessed a significant increase in the use of plastics across various life domains, resulting in a giant accumulation of plastic waste in the environment, especially in aquatic systems. In this context, microplastics and nanoparticles stand out as one of the most prominent contemporary environmental challenges due to their superior wide-scale environmental dispersal ability and bioaccumulation. This study looks at the main ways these particles are created, which come from both direct use in industries and the slow breakdown of regular plastics, as well as how they move and interact in water environments. These particles spread through waterways and coastal ecosystems, eventually settling in the oceans where they interfere with environmental components and adversely affect marine organisms across various levels of the food chain. Scientific research has revealed that these microparticles may cause blockage of the gut of marine organisms, and may also lead to serious functional disorders such as oxidative stress and impaired immune response. Worse yet, these particles can carry harmful chemical pollutants because they stick to heavy metals and long-lasting organic compounds, passing them on to living creatures. Due to the non-biodegradable, non-rapidly biodegradable nature of these substances, they pose a long-term environmental threat, the impact of which is not limited to individual organisms but extends to entire ecosystems and aquatic food webs. Human exposure to these particles —either via the food chain, inhalation, or contaminated water - has also raised serious health concerns, including intestinal disorders, immune system dysfunction, and the potential to cause endocrine disruption. Research in this field faces serious challenges, most notably the technical difficulties in monitoring nanoparticles due to their small sizes, as well as the lack of standardized and approved analytical methodologies. This study emphasizes the urgent need to intensify research and legislative efforts in this regard, and it also calls for a comprehensive review of environmental and industrial policies related to plastic production and waste management.